Substitution between Foreign Capital in China, India, the Rest of the World, and Latin America : Much Ado about Nothing? - Cravino, Javier; Lederman, Daniel; Olarreaga, Marcelo (World Bank, Washington, DC, 2012)
This paper explores the impact of the emergence of China and India on foreign capital stocks in other economies. Using bilateral data from 1990-2003 and drawing from the knowledge-capital model of the multinational enterprises to control for fundamental determinants of foreign capital stocks across countries, the evidence suggests that the impact of foreign capital in China and India on other countries' foreign capital stocks has been positive. This finding is robust to the use of ordinary least squares, Poisson, and negative binomial estimators; to the inclusion of time and country-pair fixed effects; to the inclusion of natural-resource endowments; and to the use of the sum of foreign capital stocks in Hong Kong (China) and mainland China instead of using only the latter's foreign capital stocks. There is surprisingly weak evidence of substitution in manufacturing foreign capital stocks away from Central America and Mexico in favor of China, and from the Southern Cone countries to India, but these findings are not robust to the use of alternative estimation techniques.